Primary Raynaud's phenomenon in an infant: a case report and review of literature - Castillo-Caro Paul; Sharathkumar Anjali A (BMC, 2011)
Abstract Raynaud's phenomenon (RP) is an extremely unusual finding in early infancy. In the present report we describe a one-month-old previously healthy male infant who presented with unilateral acrocyanosis. Although infantile acrocyanosis is known to be a benign and self-resolving condition, it is generally bilateral and symmetric. The unilateral nature of the acrocyanosis was an atypical finding in this infant. Consequently, he was closely monitored to evaluate the progression of his acrocyanosis. Based on his benign clinical course and failure to demonstrate other etiologies contributing to his acrocyanosis, he was diagnosed to have primary RP. Due to the rarity of RP in children, we review the progress in understanding the pathophysiology, epidemiology and management of RP and additionally discuss the differential diagnosis of unilateral and bilateral acrocyanosis in infants.